Proposal for National Reconciliation : ([S.l. : s.n.] :, 2009)
proposal presented by: National Coalition Government of the Union of Burma, National Council of the Union of Burma, Ethnic Nationalities Council, Women's League of Burma, Forum for Democracy in Burma, Students and Youth Congress of Burma, Nationalities Youth Forum.